Social Media Tiktok of Revlon Purchase Decisions: The Moderating Role of Host Personal Branding - Siti Zahra Amelia; Mohamad Hadi Prasetyo (Institute of Advanced Knowledge and Science, 2026)
The effectiveness of Revlon's marketing on TikTok social media is still not optimal. This study aims to determine and analyze the influence of TikTok social media on purchase decisions for Revlon makeup products in Bandung, as well as to analyze the role of Live Host Personal Branding as a moderating variable. The research method used is a quantitative method with a descriptive and verification approach. Data were collected through a survey of Revlon product consumers in Bandung. Data analysis was carried out using descriptive statistics and verification analysis to test the hypothesis through the T-Statistic and P-Value values. The results showed that TikTok social media had a positive and significant effect on purchase decisions, Live Host Personal Branding also had a positive and significant direct effect on purchase decisions. However, it was found that Live Host Personal Branding was not able to moderate (strengthen or weaken) the influence of TikTok social media on purchase decisions. In conclusion, Revlon product purchase decisions are directly influenced by the effectiveness of marketing on TikTok social media and the quality of the live host's personal branding as two independent factors. The company is advised to continue to improve the quality of creative content and train the persuasive communication skills of live hosts to increase positive consumer responses.